2010
DOI: 10.1111/j.1556-4029.2009.01233.x
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Irradiation as a Biological Decontaminant and Its Effect on Common Fingermark Detection Techniques and DNA Profiling

Abstract: The use of disease-causing organisms and their toxins against the civilian population has defined bioterrorism and opened forensic science up to the challenges of processing contaminated evidence. This study sought to determine the use of gamma irradiation as an effective biological decontaminant and its effect on the recovery of latent fingermarks from both porous and nonporous items. Test items were contaminated with viable spores marked with latent prints and then decontaminated using a cobalt 60 gamma irra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…For example, little is reported about the effect that decontamination procedures that remove and/or neutralize chemical agents have on forensic trace material. This lack of understanding can be partly explained by the fact that most of the research has focused on specific disinfection and sterilization techniques relating to biologically contaminated objects . Other research focused on methods to remove radiological contaminants .…”
mentioning
confidence: 99%
“…For example, little is reported about the effect that decontamination procedures that remove and/or neutralize chemical agents have on forensic trace material. This lack of understanding can be partly explained by the fact that most of the research has focused on specific disinfection and sterilization techniques relating to biologically contaminated objects . Other research focused on methods to remove radiological contaminants .…”
mentioning
confidence: 99%
“…Unfortunately, individual fingerprints were not split into irradiated/untreated halves, so that the ability to draw definitive conclusions is limited. A subsequent study [57] found no adverse effect on recovery of fingerprints on porous and non-porous materials for gamma doses up to 40 kGy (the highest dose tested). One study even showed that, for fingerprints less than 2 weeks old, there was an increase in characteristic points of about 50% after a low (unspecified) gamma dose [75].…”
Section: Potential Effects Of Radiation On Evidence: Fingerprintsmentioning
confidence: 87%
“…Due to the typeable DNA remaining, both gamma and beta irradiation were judged less effective than ethylene oxide for decontamination. In another decontamination study DNA recovery from blood and paper was approximately 5% after a gamma dose of 5 kGy (no DNA typing was reported) [57]. The range of gamma doses used was nominally 0.5, 1, 2, 3, 5, and 10 kGy.…”
Section: Potential Effects Of Radiation On Evidence: Dnamentioning
confidence: 98%
See 1 more Smart Citation
“…These lesions can prevent strand uncoiling, alter primer binding sites, and/or block DNA polymerase during PCR [14,15]. This results in allelic dropout, particularly for longer amplicons that incur DNA damage lesions with greater frequency [16], following sufficiently high doses (> 10 kGy) of γ-radiation [17,18]. multiplexed STRs is unrivalled by HVR sequencing [23,24].…”
Section: Foot Note Informationmentioning
confidence: 99%